Gadoxetic acid-enhanced high temporal-resolution hepatic arterial-phase imaging with view-sharing technique: Impact on the LI-RADS category. Issue 94 (September 2017) - Goshima, Satoshi; Noda, Yoshifumi; Kajita, Kimihiro; Kawai, Nobuyuki; Koyasu, Hiromi; Kawada, Hiroshi; Matsuo, Masayuki; Bae, Kyongtae T.
Abstract: Purpose: To evaluate the value of view-sharing multi-hepatic arterial-phase (mHAP) imaging for diagnosis of hypervascular hepatocellular carcinoma (HCC). Materials and methods: Forty-seven consecutive patients with HCC underwent gadoxetic acid-enhanced magnetic resonance (MR) imaging before angiographic and lipiodol CT. Hepatic arterial-phase images were obtained at 5 consecutive phases with shared central k-space of 25%, followed by portal venous, late (2 and 3 min), and hepatobiliary phase imaging. One-hundred-eight HCC nodules (size: 5–88 mm, mean size: 18.2 mm) confirmed on angiographic CT and lipiodol CT were evaluated for LI-RADS category and compared with single arterial-phase and mHAP findings regarding wash out, capsule, corona enhancement, and image quality. Results: Twenty-four HCCs (22.2%) (size: 6–19 mm, mean size: 12.3 mm) were categorized as LR-3 based on the single arterial-phase. Capsule appearance (25.9%) and washout (57.4%) were most frequently observed in late phase (2 min). Corona enhancement was observed in 73.1% of all HCCs on mHAP. For the 24 HCCs of LR-3, corona enhancement was observed in 75% on mHAP and contributed to upgrade category. No significant difference was found in the frequency of corona enhancement between mHAP and angiographic CT ( P = 0.11). Image quality was valued as good or excellent in all cases. Conclusion: View-sharing mHAP was feasible without compromising image quality and contributed to the improvement in diagnostic confidence for hypervascular HCC in gadoxetic acid-enhance MR imaging.